INOVASI KEBIJAKAN DESA TANGGUH COVID-19 DI KABUPATEN BANGKA - Bambang Ari Satria (Journal Publicuho, 2020)
Bangka Regency of Bangka Belitung is one of the positively confirmed areas of the 2019 Corona Virus Disease (COVID-19). However, it is one of the highest cure rate areas in Indonesia dealing with COVID-19 positive patients. This study focused on discussing how the COVID-19 resilient village policy innovation in Bangka Regency looked at three aspects that became a reference in analyzing policy innovations, namely: process aspects, method and product. This study used qualitative research method and described it descriptively-analytically. Data were collected by using in-depth interviews, observation and documentation techniques. The results showed that the innovative COVID-19 village policy in Bangka Regency was well implemented. Several factors that influenced the good implementation of COVID-19 resilient village policy innovations namely from the aspect of the process, work processes internally and externally that went well either with the certificate of village volunteers in fighting COVID-19 or not. The aspect of the method, a village gate guarded post that has been built for 24 hours to record and mobilize residents and guests. The product aspect, there was a COVID-19 resilient village program supported by village funds to explore the potential of the community so that they were empowered and able to play an optimal role for COVID-19 control.